Foreign divestment risk factors in Poland during the covid-19 pandemic - Salamaga, Marcin (Publishing House of Wroclaw University of Economics and Business, 2022)
The article is aimed at putting in order factors decisive for the risk of foreign divestment in Poland during the COVID-19 pandemic. The research covered factors regarding market, cost, industry, law, and political factors that can be important for the assessment of the risk of divestment and was based on a conjoint analysis. Such an analysis allowed for estimating the partial utilities of the surveyed companies and the subsequent calculation of the importance level of variables which represent the determinants of divestment risk. In addition, estimated partial utilities enabled the preliminary segmentation of foreign investors according to their similar preferences as to the evaluation of investment risk factors during the pandemic. Research was based on the results of a survey conducted among investors engaged in FDI in Poland with the assumption of two hypothetical scenarios of the development of the COVID-19 pandemic: optimistic and pessimistic. Based on the obtained results, it can be concluded that, irrespective of how the pandemic develops, divestment in services bears the greatest risk. The number of factors which are considered to be important determinants of foreign divestment increases along with the pessimistic scenario of the pandemic’s development including, for example, cost factors and FDI in various economic sectors.
Argumenta Oeconomica, 2022, Nr 1 (48), s. 81-100
Keywords: conjoint analysis; survey; FDI; divestment; COVID-19